Effect of a single day of increased as-needed budesonide–formoterol use on short-term risk of severe exacerbations in patients with mild asthma: a post-hoc analysis of the SYGMA 1 study. Issue 2 (February 2021) - O'Byrne, Paul M; FitzGerald, J Mark; Bateman, Eric D; Barnes, Peter J; Zheng, Jinping; Gustafson, Per; Lamarca, Rosa; Puu, Margareta; Keen, Christina; Alagappan, Vijay K T; Reddel, Helen K
Summary: Background: In mild asthma, as-needed budesonide–formoterol reduces long-term exacerbation risk compared with as-needed short-acting β2 -agonist (SABA), with a similar or increased reduction versus maintenance with budesonide plus as-needed SABA, despite a lower budesonide dose. In this post-hoc analysis of the SYmbicort Given as needed in Mild Asthma (SYGMA) 1 study, we investigated the short-term risk of severe exacerbations after a single day with various levels of reliever use. Methods: SYGMA 1 was a 52-week, double-blind, randomised, controlled, phase 3 trial, in which patients aged 12 years or older with mild asthma were randomly assigned (1:1:1) to placebo twice daily plus as-needed terbutaline 0·5 mg, placebo twice daily plus as-needed budesonide–formoterol 200–6 μg, or budesonide 200 μg twice daily plus as-needed terbutaline (ie, budesonide maintenance group). In this post-hoc analysis, we assessed the frequency of reliever use and the risk of a severe exacerbation in the 21 days after first use of more than two, four, six, or eight reliever inhalations in 24 h. SYGMA 1 is registered with ClinicalTrials.gov, NCT02149199, and is now complete. Findings: Of 5721 patients enrolled in SYGMA 1, 3849 were randomly assigned to as-needed terbutaline (n=1280), as-needed budesonide–formoterol (n=1279), or budesonide maintenance (n=1290), of whom 3836 had evaluable data (n=1277 as-needed terbutaline, n=1277 as needed budesonide–formoterol, and n=1282 budesonide maintenance). Median reliever use was 0·32 (IQR 0·08–0·91) inhalations per day for the as-needed terbutaline group, 0·29 (0·07–0·72) for the as-needed budesonide–formoterol group, and 0·16 (0·04–0·52) for the budesonide maintenance group. Compared with as-needed terbutaline, after adjustment for age, sex, randomly assigned treatment, pre-study treatment group, baseline % predicted post-bronchodilator FEV1, and severe exacerbation in the 12 months before enrolment in the study, the hazard ratio (HR) for severe exacerbation in the 21 days after a single day with more than two as-needed inhalations was 0·27 (95% CI 0·12–0·58; p=0·0008) with as-needed budesonide–formoterol and 0·39 (0·19–0·79; p=0·0091) with budesonide maintenance; after a single day of more than four as-needed inhalations the HR was 0·24 (0·10–0·62; p=0·0030) with as-needed budesonide–formoterol and 0·30 (0·13–0·72; p=0·0065) with budesonide maintenance; and after a single day of more than six as-needed inhalations the HR was 0·14 (0·02–1·06; p=0·057) with as-needed budesonide–formoterol and 0·43 (0·14–1·26; p=0·12) with budesonide maintenance. HRs were not calculated for more than eight as-needed inhalations due to the small number of events. Interpretation: In mild asthma, as-needed budesonide–formoterol reduces the short-term risk of severe exacerbations after a single day of higher use (more than two as-needed inhalations), even when overall use is infrequent. Use of an anti-inflammatory reliever might reduce the risk of short-term severe exacerbations by the timely provision of increased doses of as-needed inhaled corticosteroids and formoterol when symptoms occur. These findings should be further assessed in prospective randomised clinical trials. Funding: AstraZeneca.